The influence of Internal Factors of Consumers towards Buying Decision of Organic Vegetables - Marlinda Apriyani; Fadila Marga Saty (Jurnal Ilmiah ESAI, 2013)
Key to the success of the marketing of organic vegetables is certainly a good understanding of the behavior of consumers who consume the food products. Factors that influence public consumption of organic vegetables are Consumer internal factors such as culture, social class, individual characteristics, and psychological factors. This study aims to measure and determine the influence of internal factors on purchase decisions of consumers of organic vegetables either partially or in combination as well as reviewing internal factors are dominant in influencing consumer purchasing decisions of organic vegetables. The method of analysis used to see how the internal factors are the path analysis approach, while to see the most dominant internal consumers factors in the purchase decision of organic vegetables is Backward method Based on the results obtained (1) there is a strong influence between internal factors, namely culture, social class, individual, and psychology to the purchasing decision, but for the individual variables and produce a weak influence and (2) social class variable, individual, and psychology is the dominant variable influencing the purchase decision of organic vegetables.Keywords: organic vegetables, internal factors, path analysis